Exploring Social Media’s Impact on Societal Perceptions of Police Legitimacy and Cooperation - Debranique Mensah; James R. Jones; Veronica L. Ford (Journal of Sociological Research, 2024)
Since the 2014 killing of Eric Garner, the number of social media posts involving police officers engaging in unethical behavior has increased, and the videos and images posted have had a strong influence on the public’s perception of law enforcement officers. This paper explores the associations between the variables of social media usage, police legitimacy, and police cooperation while discussing how they intersect. In addition, this paper investigates whether these variables are still associated, after controlling for age, gender, and education. This research was conducted using a multiple regression analysis of the data collected from a quantitative survey completed by 80 participants. The participants were aged 18 and older, had an active social media account, lived in the United States, and were not former military or police officers.